Amenaza de aborto por infecciones urinarias bacterianas - Paucar Paucar, Delia Mariana (2020)
The presence of mild to moderate intensity pelvic pain that occurs during the course of pregnancy is associated with the threat of abortion due to bacterial urinary infections in pregnant women, this leads to a change in personal, family or occupational habits. The most common form of this pathology known as threatened abortion due to urinary tract infections. In our country, approximately 5% to 10% of pregnant women usually require management at the hospital level. In this study, the clinical case of a 35-year-old patient is exposed, who attends the gynecology emergency service who has been presenting since morning hours. Pelvic pain of mild to moderate intensity and about 40 minutes ago evidence of transvaginal red blood leakage with the presence of a clot of more or less 3 cm in diameter. The patient is admitted to the gynecology service where an obstetric ultrasound is requested, which reports a pregnancy of 19.1 weeks of gestation plus adequate fetal growth standards. In addition, complementary exams within which hematic biometry, urinalysis are requested, some of which reflect altered values. Intravenous hydration and complete rest of the pregnant woman are started. It is important to manage all these signs and symptoms in the most appropriate way since they could be complicated by causing a spontaneous abortion.